High Expression of RECQL Protein in ER-Positive Breast Tumours Is Associated With a Better Survival - Mahmoodi, Ardalan; Shoqafi, Ahmed; Sun, Ping; Giannakeas, Vasily; Cybulski, Cezary; Nofech-Mozes, Sharon; Masson, Jean-Yves; Sharma, Sudha; Samani, Amir Abbas; Madhusudan, Srinivasan; Narod, Steven A.; Akbari, Mohammad R. (Frontiers in Oncology, 2022)
Background RECQL (also known as RECQ1 and RECQL1) is a gene of recent interest in breast cancer and an association between high levels of RECQL protein in breast cancer tumour cells and good survival of patients has been reported. Methods To validate this association, we measured the RECQL protein levels in tumours of 933 breast cancer patients using immunohistochemistry analysis and followed the patients for death from breast cancer. Results Women with a level of RECQL protein above the 75th percentile had better 15-year disease-specific survival among ER-positive patients (62.5% vs. 48.7%, HR= 0.72, 95%CI= 0.52-0.98, p-value = 0.04), but not among ER- patients (48.9% vs. 48.0%, HR= 1.07, 95%CI= 0.67-1.69, p-value= 0.79). Among the ER-negative patients, high RECQL protein levels were associated with better survival among women who received tamoxifen treatment (67.0% vs. 51.5%, HR= 0.64, 95%CI= 0.41-0.99, p-value= 0.04). Conclusion RECQL might be a new predictive marker for tamoxifen treatment among ER-positive patients.